EXPERIMENTAL STUDY OF COMPRESSOR ENCLOSURE WITH PYRAMID ACCOUSTIC FOAM - Agus Noviana; Usman Sudjadi (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2023)
This study investigates the performance of compressor enclosures for noise absorption, reverberation, and machine ventilation to ensure a safe and healthy working environment for people. The Multi pro air compressor model BC 150 DMBW 1.5 HP is placed in an enclosure made of wood board, and for absorbing material, use 6 cm thick polyurethane pyramid foam. A fan with a flow rate of 280 CMH is used as a cooling medium and will operate simultaneously with the compressor operation. Flow Air Delivery (FAD) of the compressor is 126 L/min. The Sound Pressure Level (SPL) value is determined using a sound level meter before and after the compressor uses the enclosure. In addition, the enclosure's room temperature is recorded within 30 minutes of operation to determine whether there is a significant increase in heat to ensure that the enclosure for this compressor is still within safe limits. Based on the test results, it is known that after a 30-minute operation, the temperature rises from 29 OC to 65 OC in the inlet on the enclosure with the fan off, and the temperature rises from 29 OC to 51 OC on the enclosure with the fan on. While from the results of measuring the sound noise level, taken at a distance of 1 meter outside the enclosure, there is no significant difference, with or without using a fan, the decrease in sound noise level is only about 10 dB, which is 84 dB before using the enclosure, to 74 dB after using the enclosure. So, it can be concluded that the use of fans as coolers is quite effective in maintaining the temperature of the enclosure space when compared to natural cooling through ventilation, but the use of enclosures using pyramid foam material is not effective for reducing the noise level produced by the compressor when operating.